Red Hat Linux 9 Professional Secrets - Barkakati, Naba (John Wiley & Sons, 2011)
This ultimate under-the-hood guide to Red Hat Linux 9 takes the reader beyond obvious information about this complicated OS, revealing hidden features, tricks and alternate methods not easily found elsewhere.